ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI LOAN LOSS PROVISION BANK UMUM KONVENSIONAL DI INDONESIA (Periode 2009 – 2013) - Farida, Diana Eka; Muharam, Harjum (Faculty of Economics and Business Diponegoro University, 2016)
Bank has strategic position to support financial system stability in Indonesia. Banking main activity is collecting third party funds and then redistribute in a credit form. Lending activity makes bank faced problems when it’s implementing, one of the problem is non performing loan. To anticipate non performing loan, bank must has reserve, so the problem doesn’t directly impacting the operational activity of bank. Form of required reserve by bank is loan loss provision, so bank has to know what factor affect the amount of loan loss provision. This study analyze the effect of return on assets, loan to deposit ratio, debt to equity ratio, reserve and loan loss provision of conventional bank Indonesia in 2009 until 2013 period. Samples that are used in this study consist of 23 conventional banks in Indonesia. Regression model in this study using least square dummy variable (LSDV) including dummy of period.Result of this study shows that return on assets has negative coefficient and not significant towards loan loss provision. Loan to deposit ratio has positive coefficient but not significant so it does not effect loan loss provision while debt to equity ratio has negative coefficient and not significant to loan loas provision. Reserve has negative effect and significant to loan loss provision but it is inappropriate so the hypothesis is being rejected. Size has positive and significant toward loan loss provisions.